Intersectoral Water Allocation in the Indus Basin-Under Different Management Policies - Ringler, Claudia; Brown, Casey; Alam, Ghazi; Khan, Ahmed Fawad; Akhtar, Taimoor; Mehmood, Khalid; Yang, Yi-Chen E. (International Food Policy Research Institute, 2014)
This paper uses a hydro-agro-economic model, the Indus Basin Model Revised - Multi Year (IBMR-MY) to evaluate intersectoral water allocation in Pakistan’s Indus Basin under different surface water allocation and groundwater regulation polices. Modeling results indicate that more flexible surface water allocation policies can lead to substantial improve-ments in agricultural profits and also impact hydropower profits, but will have little impact on domestic and industrial water use benefits. Moreover, average flows to the Arabian Sea show no significant changes under this setting, which suggests that the optimal water use through flexible allocation policies will not necessarily jeop-ardize the flow for environment. We find that improving water allocation flexibility in irrigation will thus not only be crucial for improving agricultural outcomes in Pakistan, but also for sustained domestic, industrial and hydro-power generation as well as environmental outcomes. 11/11/2014 WORKING PAPER No. 024 | November 2014